PENERAPAN TEKNOLOGI PRODUKSI SIMPLISIA EMPON-EMPON, KELOMPOK TANI KECAMATAN TRAWAS, KABUPATEN MOJOKERTO, JAWA TIMUR - Mirwa Anggarani; Erlix Rakhmad Purnama; Raya Sulistyowati (Universitas Negeri Surabaya, 2019)
The community service aims to solve several main problems experienced by empon-empon farmers,namely the limited knowledge of the production techniques of empon-empon simplisia and the productionfacilities of empon-empon simplisia. These problems are experienced by partner